Effect of alkaline protease produced from fish waste as substrate by Bacillus clausii on destaining of blood stained fabric - P, Saravana kumari; R, Reshma (Journal of Tropical Life Science, 2021)
Alkaline protease or peptidases are the largest group of enzymes in biological industry with variety of application in various industries to process of raw material, dehairing, diagnosis, extraction, food production and processing, destaining, etc., where the conditions prevails above neutral pH. Because of the wider applications the demand also increases for alkaline proteases, so required to produce in large scale cost effectively. An alkaline tolerant bacterial strain Bacillus clausii was isolated from fish waste and used for mass production of alkaline protease using fish waste homogenate as media. Preliminary study on optimization of conditions for the mass production carried out. The optimum temperature for protease production ranges between 25oC and 35oC and pH determined as 9. Along with fish waste homogenate, the mass production of extracellular alkaline protease from mobilized and immobilized cells of B. clausii carried out in production media, mixture of production media and fish waste homogenate and nutrient broth as standards. The recorded results showed that the maximum enzyme production obtained immobilized cells in nutrient broth media and followed by fish waste homogenate of 8900 U/ml and 8600 U/ml respectively. Purified enzyme yield was maximum obtained from production media 0.35 g/ml.Â Blood stained cloth treated with immobilized enzyme completely removed stain compared to treatment with non-immobilized enzyme and commercially used detergent. So the current study suggests the usage of microbial alkaline protease in house hold detergent to replace usage of chemicals and save the environment from chemical pollutants.